Leaving a Legacy: Position Imprints and Successor Turnover in Young Firms - Burton, M. Diane; Beckman, Christine M. (American Sociological Review, 2007)
This article considers how local firm histories influence individual turnover rates in organizations. We argue that position imprints—the legacies left by the first incumbents of particular functional positions—constrain subsequent position holders. We show that the functional experience of the person who creates a position influences the turnover rate of successors who later occupy that position. When the first position holder has an atypical background, all successors experience high turnover rates. Individuals who are both typical with respect to the normative environment and similar to the position imprint have the lowest turnover rates. Surprisingly, we find lower turnover rates among individuals who match the position imprint even if they violate normative expectations. Thus, contrary to institutional theory predictions, we find that local firm histories dominate. In revealing how social structures emerge within firms and affect individual outcomes, our research revisits core topics of bureaucratization and organizational stratification including idiosyncratic jobs, occupational segregation, and differential mobility. In addition, we integrate structuralist and interactionist perspectives on role theory by considering how roles are created. Finally, in demonstrating the effects of position imprints on successor mobility we add a temporal dimension to theories of turnover.